Effects of the Earth's Curvature and Lunar Revolution on the Imaging Performance of the Moon-Based Synthetic Aperture Radar - Xu, Zhen; Chen, Kun-Shan (IEEE transactions on geoscience and remote sensing, 2019)
In this paper, effects of the earth's curvature and lunar revolution on the performance of the moon-based synthetic aperture radar (SAR) are examined by a comprehensive analysis of the motion-induced Doppler frequency and Doppler rate on which azimuthal imaging relies. The motion effects include the earth's self-rotation related to the earth's curvature and lunar revolution around the earth. An extended hyperbolic range equation (EHRE) is proposed in line of the equivalent velocity and equivalent squint angle, and then the signal model based on the EHRE is established to simulate the moon-based SAR image from which the imaging performance is analyzed. Theoretical analyses show that the earth's curvature is a dominant factor in determining the moon-based SAR's Doppler and azimuthal resolution. Furthermore, the earth's curvature distorts the SAR image by way of rotating the azimuth imaging from the cross-range direction within a certain skewed angle. The overall effects of lunar revolution generate a velocity correction factor and a deviate squint angle, which subsequently deteriorate the azimuthal resolution and image focusing. Results also show that effects of the earth's curvature and lunar revolution are in connection with relative positions of the ground target and moon-based SAR. To this end, numerical simulations using point target response is carried out to accentuate the necessary for taking account of the Doppler error induced by the lunar revolution.